If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9d + -4d + 1d + 6 = 3d Reorder the terms: 6 + 9d + -4d + 1d = 3d Combine like terms: 9d + -4d = 5d 6 + 5d + 1d = 3d Combine like terms: 5d + 1d = 6d 6 + 6d = 3d Solving 6 + 6d = 3d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-3d' to each side of the equation. 6 + 6d + -3d = 3d + -3d Combine like terms: 6d + -3d = 3d 6 + 3d = 3d + -3d Combine like terms: 3d + -3d = 0 6 + 3d = 0 Add '-6' to each side of the equation. 6 + -6 + 3d = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 3d = 0 + -6 3d = 0 + -6 Combine like terms: 0 + -6 = -6 3d = -6 Divide each side by '3'. d = -2 Simplifying d = -2
| 6x+3=-3+3x+18 | | 7-2^3/6-4+2 | | 7x-11=15x | | 5x+2-2x-8=12-2x-3 | | 2s+5=6s+2 | | 3x+34=13-46 | | 15+-5= | | 100+(-55)= | | -p-2=9[2-3]+6 | | -21+x=x+16 | | f/3 | | 0=40-10y | | House+car=x | | 10x=4x-8x-7 | | 92782629=1638x | | 5x-44=-44 | | (-78)+45= | | 14y+1.5x=180 | | x-4+5-9x+14-7=5 | | 8+-11= | | -(5y+3)-(4y-8)=2 | | 11-6c-5=-12 | | 5v-18-4=36 | | 3[5+4(3-y)]= | | 3.1x=3.6x-2.5 | | 9(x-5)+4=-41 | | 50=h-3 | | (x-10)/100=5 | | -10=5/12*n | | 8e^8t=10e^7t | | -4x^3-9x^2=0 | | 12y=15x-9 |